In-Person or Online? Exploring Student Pharmacists' Perceived Change in Interprofessional Skills between Two Delivery Formats - Jared Van Hooser; Anthony W. Olson (MDPI AG, 2023)
The COVID-19 pandemic drastically changed how education is delivered. Many academic programs quickly transformed their curriculum to online distance learning. This rapid transition may have compromised the rigor and fidelity of these activities. The Interprofessional Standardized Patient Experience (ISPE) is an interprofessional education activity (IPE) involving a team of students from six different healthcare professions that switched to an online delivery format. This manuscript compares pharmacy students' perceived change in interprofessional skills between the two formats. Following the ISPE, second-year pharmacy students completed the revised Interprofessional Collaborative Competencies Attainment Survey (ICCAS-R). The ICCAS-R assesses the change in interprofessional collaboration-related competencies in healthcare students before and after IPE training using a retrospective pre-post approach. For each ICCAS-R item and each delivery format (44 in-person and 51 online), paired Student's t-test on pre- and post-ISPE scores, and Cohen's d were calculated. Every item of the ICCAS-R was significant (p < 0.001), regardless of delivery format. Nearly all ICCAS-R items had a large effect size, and the remaining items had a medium effect size. The amount of change pre- and post-ISPE for each ICCAS-R item was calculated. Student's t-test was used to compare the magnitude of change in interprofessional skills between the two delivery formats. Only one difference was noted between the two delivery formats-ICCAS-R item 16, which measured actively listening to interprofessional team members (p = 0.0321). When switching to an online format, the high-fidelity dimension of the ISPE was retained. The ISPE is an effective IPE activity at increasing pharmacy students' self-perceived interprofessional collaboration skills regardless of delivery format. Even though students reported the ISPE increased their ability to actively listen to the perspectives of interprofessional team members in both formats, the magnitude of the benefit was more profound in the in-person group.